A Comparative Study between Traditional and Online Teaching-Learning: Medical Students’ Perspective in the Wake of Corona Pandemic - Rawat, Ranu; Singh, Parmal (National Journal of Community Medicine, 2020)
Background: Teaching for the students may be either taken up traditionally in a classroom or online. This study was aimed to compare the perspectives of medical students regarding Traditional and Online Teaching-Learning and to explore the association between the perception of the students regarding the preferred method and their respective genders. Material and Methods: The study was conducted on 3rd year MBBS students of Adesh Medical College and Hospital, Shahabad (M), Kurukshetra using a self designed semi-structured questionnaire for data collection. Results: A higher proportion of students agreed that online teaching as compared to traditional teaching was more convenient, more cost-effective, more time-consuming, more tiring ,more prone to distractions, provides more learning and has more retention while a higher proportion of students disagreed that online teaching as compared to traditional teaching was more interesting, more motivating, more satisfying and provides for more understanding. A significant association was detected between a few crucial variables and gender of the students. Conclusions: Clear cut superiority of either method could not be conclusively established. Majority of the students responded in favour of mixed or blended learning. This method could be explored in future. To iron out the effect of gender on the differing perspectives, upgrading the technology know-how of the students coupled with counseling could be resorted to.